2014
DOI: 10.17269/cjph.105.4242
|View full text |Cite
|
Sign up to set email alerts
|

Youth health care utilization in Nova Scotia: What is the role of age, sex and socio-economic status?

Abstract: Y outh, who experience major changes in physical, mental and social development, 1,2 have distinct and unique health care needs related to this critical transition period in their development. 3,4 These needs are often not well met within a framework that is designed either for children or adults. 5 Changes in health, including an increased burden of mental disorders, increasing autonomy and an emerging capacity for self-initiated health-seeking behaviour, are all features of the transition period from child t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The social background of a family significantly impacts family residence, health care use or access, parenting, and, directly and indirectly, child behavior and development [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A central indicator of a family’s social background is the socio-economic status (SES), which is usually reflected by parents’ education, occupation, and (equivalent household) income [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The social background of a family significantly impacts family residence, health care use or access, parenting, and, directly and indirectly, child behavior and development [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A central indicator of a family’s social background is the socio-economic status (SES), which is usually reflected by parents’ education, occupation, and (equivalent household) income [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, seven studies found females were higher resource users than males and six found that sex-based differences were dependent upon other factors. Females were identified as higher resource users in multiple health care settings, including health services for all ages [16,17,21,22,28], health services for youth [29,30], primary care for all ages, and adult emergency department presentations [21,31].…”
Section: Sexmentioning
confidence: 99%
“…Women also had longer hospitalizations [17,20,2332]. Manos (2014) examined sex-based different in a population aged 12-24 years old in Nova Scotia, Canada. Females accounted for 2X more primary care and inpatient contacts and made up 84% of all high-resource users [29].…”
Section: Sexmentioning
confidence: 99%
See 2 more Smart Citations